Unraveling the connection between endocrine-disrupting chemicals and anxiety: An integrative epidemiological and bioinformatic perspective - Ziang Guo; Yuxuan Tan; Chuhang Lin; Haiying Li; Qianqian Xie; Zhengtian Lai; Xiao Liang; Lei Tan; Chunxia Jing (Ecotoxicology and Environmental Safety)
Background: The evidence linking endocrine-disrupting chemicals (EDCs) to anxiety in adults is currently sparse, while the effects of various categories of EDCs on the risk of anxiety, along with the underlying mechanisms, remain poorly understood. Methods: Four EDCs—polycyclic aromatic hydrocarbons (PAHs), phenols, pesticides, and phthalates—were quantified in 3927 adults from the National Health and Nutrition Examination Survey (NHANES) (2007–2012). We employed five statistical models to assess the individual and joint impacts of EDCs on anxiety risk. Causal mediation analysis frameworks were constructed to explore the mediating role of oxidative stress (OS). We identified potential biological mechanisms linking analytes to outcomes using the Comparative Toxicogenomics Database (CTD), MalaCards, and Open Targets, followed by enrichment analyses with Gene Ontology (GO) and the Kyoto Encyclopedia of Genes and Genomes (KEGG). Results: In individual chemical analyses, nine PAHs were significantly associated with increased anxiety risk (P < 0.05). Mixed-effects analyses showed that co-exposure to EDCs positively correlated with anxiety, primarily due to 2-hydroxyfluorene (2-FLU) and 3-hydroxyfluorene (3-FLU). Bilirubin mediated 5.42 % of the anxiety linked to the PAH mixture. The inflammatory genes TNF and IL-6 were identified as key biological stressors, with enrichment analysis indicating significant involvement in reactive oxygen species metabolic processes and the AGE-RAGE signaling pathway. Conclusion: This study highlights the association between EDCs and anxiety in a representative U.S. population, indicating that exposure to PAHs may elevate anxiety risk through OS, inflammation, and the AGE-RAGE signaling pathway. Further longitudinal study were merited to support our results.